Edukasi Nilai-nilai Etika dan Moral pada Siswa SMP - Shirley Azi Astuti; Manda Amelia Putri; Syachreza Alvaridzy Mohamad Elradin; Muhammad Refanza Mahyudin; Grace Natasya Br Sembiring; Dealova Indra Wardiana; Radithya Yoga Widyanto; Restu Andini; M. Reyhan Rama Adira; Lutfi Hardiyanto (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
PJBL activities with the theme “Education of Ethical and Moral Values in Junior High School Students have been successfully implemented at SMPN 174 Jakarta. We took this theme with the aim of educating students how important ethics and morals are in everyday life. How to dress and how to speak to teachers, parents, friends and others. Our group conducted the service by presenting material about the value of ethics and morals, as well as making questionnaires and interacting in the form of questions and answers with students. Here we focus on one class, namely class 8H with 31 students. This service has been fairly successful because the students are very enthusiastic about participating in our activities.